A Simple Method to Reduce Mesh Dependency in Modelling Landslides Involving Brittle Soils. Issue 4 (9th June 2022) - Troncone, A.; Pugliese, L.; Parise, A.; Conte, E.
Abstract : This paper focuses on the numerical simulation of the deformation processes occurring in the slopes when soils with strain-softening behaviour are involved. In these circumstances, a progressive failure may occur with the consequent motion of the unstable soil mass in the post-failure stage. This problem can be only solved using advanced numerical techniques capable also of accounting for the occurrence of large deformations. However, the solution is generally mesh dependent and may be affected by lack of convergence. In the present study, the material point method (MPM) is employed to simulate the occurrence of large deformations, in conjunction with a strain-softening Mohr-Coulomb constitutive model, in which the shear strength parameters are reduced as a function of the accumulated deviatoric plastic strain, and a model parameter controlling the rate of strength decrease. To evaluate this parameter and to reduce the effects of the mesh dependency on the numerical solution, a novel procedure based on the results of direct shear tests is presented. This methodology is completely analytical and requires few parameters with a clear physical meaning and of simple experimental determination. Some simulations are performed to assess the reliability of the proposed procedure.